2008
DOI: 10.1016/j.cca.2007.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Pseudohyperphosphatemia associated with high-dose liposomal amphotericin B therapy

Abstract: Background-Acute increases in serum inorganic phosphorus (Pi) up to 4.75 mmol/l in the absence of hypocalcemia and tissue deposition of calcium phosphate were noted in 3 patients receiving liposomal amphotericin B (L-AMB). We investigated L-AMB as a possible cause of pseudohyperphosphatemia.Methods-Serum samples from the index patient were analyzed for Pi content by our laboratory's primary analyzer (Synchron LX20 ) and by an alternate analyzer (Vitros). Clear and lipemic serum pools, and normal saline, were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 22 publications
1
21
0
1
Order By: Relevance
“…Furthermore, treatment with high dose of liposomal amphotericin B and sample contamination with recombinant tissue plasminogen activator or heparin have been implicated as causes of spurious hyperphosphatemia [64,65,66]. Liposomal amphotericin B-related pseudohyperphosphatemia is attributed to the interference of the drug in the Synchron LX-20 phosphorous assay.…”
Section: Pseudohyperphosphatemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, treatment with high dose of liposomal amphotericin B and sample contamination with recombinant tissue plasminogen activator or heparin have been implicated as causes of spurious hyperphosphatemia [64,65,66]. Liposomal amphotericin B-related pseudohyperphosphatemia is attributed to the interference of the drug in the Synchron LX-20 phosphorous assay.…”
Section: Pseudohyperphosphatemiamentioning
confidence: 99%
“…Liposomal amphotericin B-related pseudohyperphosphatemia is attributed to the interference of the drug in the Synchron LX-20 phosphorous assay. In such cases, normal values are found after removing the liposomal amphotericin B from the samples by ultrafiltration [65]. Alternatively, a different analyzer should be used for the accurate measurement of phosphate levels.…”
Section: Pseudohyperphosphatemiamentioning
confidence: 99%
“…The next chapter in this book deals in significant detail about TLS. Of note, pseudohyperphosphatemia has been reported in patients with paraproteinemias and in patients receiving high dose of liposomal amphotericin B for treatment of severe fungal infections [96,104]. The former appears to be the result of interference between the abnormal proteins and the laboratory assay.…”
Section: Hyperphosphatemia Case #6mentioning
confidence: 97%
“…Two in vitro studies demonstrated a dose-dependent, linear rise in phosphorus measurements when serum was spiked with LAmB. A 0.0072-to 0.0090-mmol/liter increase in phosphorus correlated with a 1-mg/liter increase in LAmB concentration (8,10). No effect was observed using a comparable placebo molecule without active drug, leading the authors to conclude that active drug in the liposomal formulation (LAmB) is involved in the assay interference (10).…”
mentioning
confidence: 99%
“…The liposomal formulation of amphotericin B (LAmB; AmBisome) may be preferred over other formulations due to a more favorable side effect profile and enhanced tissue penetration, but it is still associated with hypokalemia, likely attributable to increased tubular permeability to monovalent cations, and hypomagnesemia, for which the mechanism is less certain (1)(2)(3). Although the drug is known to cause hypophosphatemia as well, several reports of hyperphosphatemia and pseudohyperphosphatemia have been published (1,(4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%